Respostas

2014-03-08T18:47:38-03:00

a)9^-1.9^1 (mesma base, apenas some os expoentes e mantenha a base) -1 + 1 = 0
   9^0
   = 1
b)4^-1.4^-2.4^-3  (mesma regra) -1 -2 -3 = -6
    = 4^-6
c)a^n.a^-m.a^p (mesma regra) n- m + p
   = a^n- m + p
d)x^5.1/x^3.x^4.1/x (mesma regra)
   x^5. x^-3. x^4 . x^-1           ----------   5 - 3 + 4 - 1 = 5
    = x^5
e)
1/a^2.a^3 (mesma regra)
   a^-2.a^3                      ------------  -2+3 = 1
   = a
f) 
x^-2.x^3.x^-1 (mesma regra) -2 + 3 - 1 = 0
  x^0
= 1
g)
3^4.1/3^-2.3^-4.3 (mesma regra)
   3^4. 3^2. 3^-4. 3^1     ------------- 4 + 2 - 4 + 1 = 3
   3^3
 = 27